Deteksi Dan Isolasi Escherichia coli Resisten Ampisilin Yang Diisolasi Dari Peternakan Ayam Di Surabaya, Indonesia - Tridiganita Intan Solikhah (Jurnal Farmasi Indonesia, 2020)
The study was carried out to isolate and detect the resistance of E. coli bacteria from four livestock in Surabaya, Indonesia. This research used 40 samples of chicken thigh meat. The first step is isolated Escherichia coli bacteria using BGBB media (Brillilliant Green Bile Broth), and then used EMBA (Eosin Methylen Blue Agar) media for confirmatory tests, IMViC tests (Indole, Methyl Red, Voges Praskauer, and Citrat) to identify the enterobacteriaceae bacteria, and performed the gram staining test. Determined the Escherichia coli sensitivity to antibiotic by using disk diffusion method. Resistance test has resulted for ampicillin against E.coli is 100% resistance in all farms. In this research 13 of 40 samples from chicken meat had positive E.coli. The result from electrophoresis product of PCR said that resistance Escherichia coli had a specific band. Total 13 samples of positive Escherichia coli resistance ampicillin has specific DNA band primary shv with 768 bp in length.